Population Pharmacokinetics and Model-Based Dose Optimization of Vancomycin in Sudanese Adult Patients with Renal Impairment - Ahmed KA; Ibrahim A; Gonzalez D; Nur AO (Dove Medical Press, 2024)
Khalid Altigani Ahmed,1 Alnada Ibrahim,2 Daniel Gonzalez,3 Abubakr O Nur4 1Department of Clinical Pharmacy, College of Pharmacy, Najran University, Najran, Saudi Arabia; 2Department of Pharmacy Practice, College of Pharmacy, Princess Nourah bint Abdulrahman University, Riyadh, Saudi Arabia; 3Division of Clinical Pharmacology, Department of Medicine, Duke University School of Medicine, Durham, NC, USA; 4Department of Pharmaceutics, Faculty of Pharmacy, University of Khartoum, Khartoum, SudanCorrespondence: Alnada Ibrahim, Department of Pharmacy Practice, College of Pharmacy, Princess Nourah bint Abdulrahman University, P.O. Box 84428, Riyadh, 11671, Saudi Arabia, Email alaibrahim@pnu.edu.saPurpose: The study aimed to perform a population pharmacokinetic (PK) analysis to obtain vancomycin PK parameter estimates in Sudanese adult patients. The population PK model is then applied to perform model-based dose optimization.Patients and Methods: Data were collected through a retrospective, single-center, observational cohort study performed in Aliaa Specialist Hospital, Khartoum, Sudan. A population PK model was developed using the MonolixSuite 2020R1 to explore the potential effects of demographics and laboratory covariates on vancomycin PK. Monte Carlo simulations were performed to optimize dosage regimens as a function of creatinine clearance (CLcr) and virtual patients were partitioned into five CLcr groups.Results: We retrospectively collected 194 vancomycin plasma concentrations from 99 adults. The median (interquartile range) for age (years) and CLcr (mL/min) were 65 (50- 75) and 12.7 (5.52- 25.78), respectively. Vancomycin PK data were best fitted using a one-compartment model with linear elimination. The estimates of clearance and volume of distribution were 2.02 L/h and 65 L, respectively. CLcr was identified as the main covariate explaining the PK variability in vancomycin CL. CL significantly decreased with decreasing CLcr. For the five CLcr groups evaluated, a tailored vancomycin daily maintenance dose (using patients' CLcr) ranged from 200 to 1650 mg. Overall, simulations showed that 45% (CI; 41.11- 47.36%) of patients would achieve a target AUC with the suggested dosages.Conclusion: A population PK model of vancomycin was developed using data obtained from adult Sudanese patients. Model-based dose optimization can aid clinicians in selecting initial vancomycin doses that will maximize the likelihood of a favorable treatment response.Keywords: vancomycin, dose individualization, monitoring, pharmacokinetics dosing, pharmacometrics